STUDY OF FACTORS INFLUENCING NON-MUSLIMS BUYING BEHAVIOR TOWARDS HALAL PRODUCTS IN INDONESIA - Miharja, Ghianinda; Lestari, Yuliani Dwi (Journal of Business and Management, 2017)
Abstract.With the high amount population of Muslims in Indonesia which represnt the majority of its population, the demand towards halal products are relatively high. However, as a minority, non-Muslims that are given this circumstance where the condition demands high amount halal products may given no other choice than choosing halal product. This study aims to find out the factor influencing purchasing halal product in Indonesia from non-Muslim perspective and their actual purchase. To reach this objective, this study applies the Theory of Planned Behaviour as the basic theoritical approach. The result of this study shows that the non-Muslim’s subjective norms doesn’t have have direct effect toward halal purchasing intention while their perceived behaviour does not directly influence the actual halal purchase.  Keywords: : halal products, theory of planned behaviour, Indonesia